(3fhQ GdYjhf hLGeY Gdafhfs - (3CHh RcQjG jMji Hf CHj GdQLG GdWHjHs
(3ChdgG (B:s
(3GdMeO ddg GdPi aWQ GdSeGA hRjfgG HGdfLhe hGdRhGgQ CeG HYO adeG JCedJ Ndbg GdEfSGf heG QcH Gddg JYGdi ajg hSejJg fhQ GdYjhf hLGeY Gdafhf dCffi ChOYJ ajg ef cdGe GdaGVd LGdjfhS hOjhSbhQjOhS hGdQGRi GdHGH GdChd ai GdQDhS GdKeGfjI GdJi s
(3BNQgG (B:s
(3jfJgi HGdHGH GdKGdK hGdYTQhf ai gjFI GdLaf hMQcJg s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdhWfjI s
Keywords: (3GdWHs